Roots take up labeled nitrogen from a depth of 9 m in a wooded savanna in Brazil - Pinheiro, Rafael Costa [UNESP]; Bouillet, Jean-Pierre; Regina Pivello, Vânia; Aló, Lívia Lanzi [UNESP]; Costa, Vladimir Eliodoro [UNESP]; Van den Meersche, Karel; Guerrini, Iraê Amaral [UNESP]; Laclau, Jean-Paul [UNESP] (Elsevier, 2021)
The savannas (called Cerrado) are the second-largest vegetation formation in Brazil after the Amazon rainforest, with about 2 million km2. Roots have been found in very deep soil layers in Cerrado ecosystems, which suggests a crucial role of deep rooting in the supply of water and nutrients over dry periods. The aim of our study was to gain insight into the complementarity of common Cerrado woody species in taking up mobile nutrients throughout deep soil profiles. In a closed-canopy savanna with dense woody understory, labeled nitrate was injected into the soil at six soil depths (0.1, 1.5, 3.0, 6.0, 9.0, or 12.0 m) with three plots per depth, at two dates (in rainy and dry seasons). Five months after labeled nitrate injection, young leaves were sampled and foliar δ15N was determined in each plot in the three most common woody species (Coussarea hydrangeifolia, Miconia albicans and Xylopia aromatica). The maximum depth of 15N uptake was dependent on the species. X. aromatica trees took up 15N from a maximum depth of 9 m and exploited a much larger soil volume than the two other species, with the uptake of 15N at a horizontal distance of up to 5 m between the trunk and the injection site. The behavior of M. albicans and C. hydrangeifolia was similar, with a strong uptake of 15N only in the 0–1.5 m soil layer, within 2 m horizontally from the injection site. The depth of 15N uptake over the dry season was not related to the diameter at breast height of the woody plants sampled. We show that roots can take up labeled nitrogen from a depth of 9 m in tropical wooded savannas, which suggests an important role of deep-rooted species in closing biogeochemical cycles on highly weathered tropical soils.
Keywords: 15N; Cerrado; Deep roots; Nutrient; Subsoil; Tropical savanna